THE EFFECT OF SUGAR CONCENTRATION AND DRYING TIME TO NATA DE COCO CHARACTERISTIC - Eka Lidiasari; Ina Permata Sari; Nindia Febianti; Boby Pranata (Universitas Muhammadiyah Semarang, 2026)
Nata de coco is a fermented food product rich in cellulose produced by Acetobacter xylinum and commonly utilized as an ingredient in various beverages and desserts. Despite its popularity, the high moisture content of fresh nata de coco results in limited shelf life and challenges in storage and transportation. Drying is considered a suitable approach to improve product stability and extend its storage period. This study aimed to determine the influence of sugar concentration and drying time on the physical and chemical characteristics of dried nata de coco. The experiment was arranged using a factorial completely randomized design with two factors: sugar concentration (40%, 50%, and 60% w/v) and drying time (7, 8, and 9 hours), each treatment performed in three replications. The evaluated physical properties included texture, color parameters (L*, a*, and b*), and rehydration capacity, while chemical properties consisted of moisture content and total sugar. The results revealed that sugar concentration significantly affected lightness (L*), rehydration capacity, moisture content, and total sugar levels. Drying time significantly influenced texture, color (L* and a*), rehydration capacity, moisture content, and total sugar. No significant interaction between the two factors was observed. The best treatment was obtained at 40% sugar concentration with a drying time of 7 hours, resulting in dried nata de coco with favorable physical and chemical characteristics